Existence and iteration of a positive solution to a second‐order quasilinear problem - Yao, Qingliu (Mathematical Modelling and Analysis, 2010)
A successive iteration sequence of positive solution is structured for a singular second‐order quasilinear problem. The sequence can converge uniformly to the positive solution of the problem. Main tools are the Hammerstein integral equation and the monotone iteration technique on cone. The iteration sequence starts with known constant function and, therefore, is useful in computation analysis.First published online: 14 Oct 2010